The effect of boiled false yam tuber meal on feed digestibility and egg laying performance of Lohmann Brown Layer Chickens - Mohammed, Alhassan; Nani, I.A; Dei, H.K (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2024)
An experiment was conducted to determine feed digestibility and egg laying performance of layer chickens fed diets containing boiled false yam tuber meal (BFYTM). The false yam tubers were peeled with a knife and chopped into small chips ( 2 cm), boiled for 2 hours in boiling water, sun-dried to a moisture content of about 12% and ground into a gritty meal. The BFYTM replaced maize at dietary levels of 0, 50, 75 and 100 g/kg in maize-fishmeal based diets. At 20 weeks of age, 16 Lohmann brown layer chickens were randomly allotted to the four dietary treatments in a Completely Randomized Design, with one hen per cage for the digestibility trials using the total collection method. At 19 weeks of age, 240 Lohmann brown pullets were randomly allotted to the four dietary treatments and fed diets containing BFYTM which replaced maize at dietary levels of 0, 50, 75 and 100 g/kg in maize-fishmeal based diets for 16 weeks. Each treatment replicated four times in a Completely Randomized Design, with initial mean live weight of 1.45 kg per bird per replicate. The birds were housed in deep litter pens. Feed and water were provided ad libitum from 19 to 35 weeks of age. Data collected were subjected to one-way Analysis of Variance (ANOVA) using GenStat. There was no significant (p>0.05) difference in the dry matter digestibility among treatment groups. The crude protein digestibility was not significantly (p>0.05) different between control birds and birds fed 50 g/kg BFYTM diet, but higher (p<0.05) than those birds fed diets containing 75 and 100 g/kg BFYTM diets. Hens on the 50 g/kg BFYTM diets exhibited a higher (p<0.05) fat digestibility than those on the control diet and their counterparts fed the 75 and 100 g/kg BFYTM diets. Ash digestibility was lower (p<0.05) for birds fed the control diets than those birds fed BFYTM based diets, but similar (p>0.05) ash digestibility was recorded within the diets containing BFYTM. Mean feed intake of the hens was similar (p>0.05) for all treatments. Mean egg weight and mortality were not significantly different (p>0.05) among treatments. Mean hen-day egg production, egg mass and feed efficiency of the control birds were higher (p<0.05) than those of their counterparts fed the BFYTM-based diets. Based on this study, it can be concluded that 50 g/kg BFYTM in the diet of layer chickens had no adverse effect on nutrient digestibility of feed, but had adverse effect on egg production.